Fostering a Culture of Sustainability: The contribution of internal sustainability communication in promoting sustainable development – a case study - Teichrieb,Johanna (2025)
A profound transformation toward sustainability is reshaping society. In every industry, organizations increasingly depend on Sustainable Development Goals (SDGs) and Environmental Social Governance (ESG) standards as crucial bench- marks to guide their operations. Making sustainability a core priority in corporate operations also involves integrating it into corporate communications. Internal communication practitioners play an essential role in leading internal sustainable development, functioning as incubators that nurture, facilitate, and protect emerging sustainability initiatives within organizations. Much like a hen sitting on an egg, providing the right conditions for the egg to hatch, communicators create an environment to bridge the gap between intention and action, translating sustainability initiatives into tangible behavioral and cultural changes. To investigate this phenomenon, six internal communication practitioners and six employees of a large-size company in Germany were interviewed regarding the intention and perception of internal sustainability communication functions. The findings reveal that bridging strategic intent with employee experience takes information and education (providing), shared purpose and community (connecting), as well as behavioral engagement and recognition (supporting). A fourth category emerged from the data, highlighting the need for organizational coherence and role clarity (structuring). Each function supports the others while neglecting one risks weakening the entire system. This reflects the idea that employees act on sustainability not in isolation, but through an interplay of messages, norms, structures, and identities. Organizations seeking to transform their organizational culture toward sustainability need to invest not only in messaging but in employee engagement, support, and community-building.
Keywords: Internal sustainability communication; culture of sustainability; communicators as incubators; sustainable development